Market Reaction to the Fed Quantitative Easing Policy: Indonesian Evidence - Sevanrhoo Noya Dean Tanardi; Irwan Trinugroho (Sebelas Maret Business Review, 2017)
We examine the information content of the announcements of quantitative easing policy by The Fed in 2008, 2010 and 2012 on the stock price of firms listed in the Indonesia Stock Exchange, more particular firms with liquid stocks included in the list of LQ45. Moreover, we also investigate the determinants of abnormal return by focusing on the effect differences between foreign-controlled and domestic firms as well as between crisis and non-crisis period. Event study and OLS regression are employed to examine our hypotheses. We find that there are significant abnormal returns around the announcement dates both during the crisis and non-crisis period. No evidence is found on the difference between foreign-controlled and domestic firms.